Relationships among TQM practices and Performance, considering the influences of the Culture, the Industrial Sector and the Size of the Firms - Pino Jordán, Ricardo Miguel (2015)
The purpose of this study was to propose a model for understanding the relationships among the Total Quality Management (TQM) Practices and the Performance, considering the culture, the industrial sector and the size of the firms. After the evaluation of the proposed model in a specific developing country, some conclusions were the following: (a) TQM Practices had a significant relationship with the operational performance of the private firms, but not for all types of firms, (b) TQM practices which were most related with the operational performance of firms which produced services: (i) in small firms were: the training of the workers, the management commitment, and the customer focus, (ii) in medium firms were: quality management of providers, product design, and the management commitment, and (iii) in the big firms were: product design, management commitment and customer focus, and c) TQM practices which were most related to the operational performance in medium and big firms were: customer focus, product design and training of workers. Finally, some topics were suggested for future researches.